Accounting for global value chains: rising global inequality in the wake of COVID-19?. Issue 6 (2nd November 2021) - Court, Christa D.; Ferreira, João-Pedro; Hewings, Geoffrey J.D.; Lahr, Michael L.
ABSTRACT: Production processes depend on fragmented and interdependent value chains; nowadays, a single product often includes components produced in dozens of countries. Many public health measures being implemented to prevent the spread of COVID-19 have dampened economic activity of 'non-essential' sectors. The decreased production affects other industries and countries that supply parts, machinery, and services via global value chains. Using the World Input-Output Database, we show how a hypothetical decline in the worldwide consumption of a set of non-essential sectors affects the global distribution of GDP and employment. While richer countries consume relatively more non-essential goods and services, we find, by considering the interdependencies among developed and developing economies, that low-income countries are likely to suffer steeper declines in their GDP and employment. Specifically, for each 1% decline in the demand for non-essential products, the GINI index across nations is expected to rise by 0.3%. That is, global inequality is likely to rise, contradicting some earlier findings. Finally, we show that economies with less-diverse sets of industries are more vulnerable to such global shocks. This study highlights the role of value chains in analyzing the spatial spread of the impacts and their contribution to amplifying world imbalances.